Oxidative stability and its relationship with natural antioxidants during refrigerated retail display of beef produced in Argentina - Insani, Ester Marina; Eyherabide, A.; Grigioni, Gabriela Maria; Sancho, Ana Maria; Pensel, Norma Ana; Descalzo, Adriana Maria (Elsevier, 2019)
The objective of this study was to determine if pasture or grain diets affect oxidative/antioxidative status and the color stability of beef during retail display. Ten crossbreed steers were fed on pasture. Five of them were randomly assigned to remain on this diet, and the other five were finished on feedlot system (grain diet) during 110 days until slaughter. Slices of Psoas major steaks were randomly distributed among retail display times (1, 3, 5, 7 and 9 days). Lipid and protein oxidation were higher in Psoas major steaks from grain diet than in pasture diet (P < 0.05). After 3 days of display, lipid oxidation increased in meat from grain diet, whereas in meat from pasture diet the first evidence was after 7 days (P < 0.05). Protein oxidation was higher in meat from grain diet than in meat from pasture diet at day 9 of display (1.15 ± 0.92 vs. 1.91 ± 0.70 μg/g, respectively; P < 0.05). Antioxidant vitamins, α-tocopherol and β-carotene were higher at time = 0 in pasture Psoas major steaks (P < 0.05) and were differentially reduced throughout storage. While α-tocopherol decreased 41% and 57% for pasture and grain beef respectively (P < 0.05), β-carotene levels remained practically unaffected in grain beef. After 7 days of display “a” value was higher for Psoas major steaks from pasture diet (P < 0.05). Besides, “L” parameter showed higher values for samples from grain diets but it was no affected by display time. No differences were observed between both treatments for “b” value, but a significant decrease (P < 0.05) was observed along storage.